Improved Monosegment Pedicle Instrumentation for Treatment of Thoracolumbar Incomplete Burst Fractures. (4th May 2015) - Liu, Liehua; Gan, Yibo; Zhou, Qiang; Wang, Haoming; Dai, Fei; Luo, Fei; Hou, Tianyong; Zhang, Chengmin; Zhao, Chen; Zhang, Jinsong; Xu, Jianzhong; Lü, Yingwen
Abstract : Aim . Comparing the clinical results of improved monosegment pedicle instrumentation (iMSPI) and short-segment pedicle instrumentation (SSPI) retrospectively. Method . 63 patients with thoracolumbar incomplete burst fracture were managed with iMSPI or SSPI. 30 patients were managed with iMSPI and fusion. 33 patients were managed with SSPI and fusion. Operative time, blood loss, postoperative drainage, and complications were recorded. Percentage of anterior body height compression (ABHC%) and sagittal index (SI) were obtained preoperatively, one week postoperatively, and at the last followup. Results . The blood loss and postoperative drainage were significantly less in the iMSPI group than in SSPI group ( P < 0.05 ) . The follow-up duration of the two groups was not significantly different ( P > 0.05 ) . At 12 months postoperatively posterolateral fusion was obtained satisfactorily. Neither preoperative ABHC% and SI nor postoperative SI were significantly different ( P > 0.05 ), but there was a significant difference in postoperative ABHC% ( P = 0.000 ) . The ABHC% and SI were not significantly different between the two groups at the last followup ( P > 0.05 ) . There were no fixation failures or other complications. Summary . IMSPI yielded satisfactory results similar to those of SSPI in patients with type A3.1/3.2 thoracolumbar fractures. IMSPI is recommended for minor trauma, reducing one-segment fusion, and maximization of the remaining motor function.